2012
DOI: 10.3184/095422912x13394368814321
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and distribution of Cd, Cu, Pb and Zn in the soft tissue and shell of oysters collected from the northern coast of Qeshm Island, Persian Gulf, Iran

Abstract: A study was conducted to determine the bioaccumulation and relationships of some essential and non essential metals in the different tissues of Saccostera cucullata to sediments by calculating their biota-sediment accumulation factor (BSAF) values and the correlation analysis. For this study, 53 rocky oysters (Saccostrea cucullata) and 15 surface sediment samples were collected from four stations in May 2010 of the intertidal zones of Qeshm Island, Persian Gulf, Iran. The results indicate that the highest BSAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Previous study has reported that, oyster C. virginica, was unable to eliminate accumulated metals from their soft tissue even after depuration [49]. This condition is attributed to the presence of metallothionein, a cysteine-rich protein that has high affinity to heavy metals [50] which accumulate inside the cells in a non-toxic form [49]. Metallothioneins are responsible in the homeostasis of essential metals (Zn and Cu), detoxification of toxic metals (especially Cd) as well in scavenging free radicals [51].…”
Section: Metal Pollution Indexmentioning
confidence: 98%
“…Previous study has reported that, oyster C. virginica, was unable to eliminate accumulated metals from their soft tissue even after depuration [49]. This condition is attributed to the presence of metallothionein, a cysteine-rich protein that has high affinity to heavy metals [50] which accumulate inside the cells in a non-toxic form [49]. Metallothioneins are responsible in the homeostasis of essential metals (Zn and Cu), detoxification of toxic metals (especially Cd) as well in scavenging free radicals [51].…”
Section: Metal Pollution Indexmentioning
confidence: 98%
“…Nedjelja (2.44 µg g −1 ) and Cogi (2.57 µg g −1 ) were higher than in conchixes of mussels from the same locations (2.07 µg g −1 and 1.6 µg g −1 , respectively). Mussels filter high amounts of water daily; therefore, they accumulate trace metals, which contribute to much higher content in the soft tissues than in ambient water [39]. However, despite different accumulation capacities, both soft tissues and shells can be used as bioindicators due to their ability to accumulate metals [40].…”
Section: Discussionmentioning
confidence: 99%
“…As coastal populations grow and the use of prescription and nonprescription pharmaceuticals continues to rise (Gu et al, 2010), it is increasingly important to develop effective monitoring strategies and tools to detect changes and understand the effects of multiple contaminants on marine organisms and the humans who consume them. (Shirneshan and Bakhtiari, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The PCA was performed in R version 3.1.3 (R Development Core Team, 2015). Biota-sediment accumulation factors (BSAFs) compare the concentration of a given contaminant measured in an organism to the concentration of the contaminant measured in the sediment (Shirneshan and Bakhtiari, 2012). BSAFs were calculated by dividing the summer 2013 oyster tissue concentration by the sediment concentration.…”
Section: Quality Control and Reportingmentioning
confidence: 99%
See 1 more Smart Citation